NATURAL VARIATIONS OF SE ISOTOPIC COMPOSITION DETERMINED BY HYDRIDE GENERATION MULTIPLE COLLECTOR INDUCTIVELY COUPLED PLASMA MASS SPECTROMETRY - Rouxel O.; Ludden J.; Carignan J.; Marin L.; Fouquet Y. (My University, 2002)
Multiple-collector inductively coupled plasma mass spectrometry has been used for the precise measurement of the isotopic composition of Se in geological samples. Se is chemically purified before analysis by using cotton impregnated with thioglycollic acid. This preconcentration step is required for the removal of matrix-interfering elements for hydride generation, such as transitional metals, and also for the quantitative separation of other hydride-forming elements, such as Ge, Sb, and As. The analyte is introduced in the plasma torch with a continuous-flow hydride generation system. Instrumental mass fractionation is corrected with a ''standard-sample bracketing'' approach. By use of this new technique, the minimum Se required per analysis is lowered to 10 ng, which is one order of magnitude less than the amount needed for the N-TIMS technique. The estimated external precision calculated for the 82Se/76Se isotope ratio is 0.25%% (2σ), and the data are reported as delta notation (%%) relative to our internal standard (MERCK elemental standard solution). Measurements of Se isotopes are presented for samples of standard solutions and geological reference materials, such as silicate rocks, soils, and sediments. The Se isotopic composition of selected terrestrial and extraterrestrial materials are also presented. An overall Se isotope variation of 8%% has been observed, suggesting that Se isotopes fractionate readily and are extremely useful tracers of natural processes.